Measly middle ages - Deary, Terry; Brown, Martin (London : Scholastic, 2016)
"All the foul facts about the Measly Middle Ages are ready to uncover, including why chickens had their bottoms shaved, a genuine jester's joke and what ten-year-old treacle was used for..."--Publisher description
Includes index
Primary
900-999
Keywords: Middle ages -- Juvenile literature; Middle ages -- Social life and customs -- Juvenile literature; Great Britain -- History -- Medieval period, 1066-1485 -- Juvenile literature